Ответы и объяснения

Лучший Ответ!
2012-04-08T07:40:54+04:00

2(а+2)-10=6(3-а)                                 3(2у-1)+6(3у-4)=83+5(у-3)

2а+4-10=18-6а                                    6у-3+18у-24=83+5у-15

2а+6а=18-4+10                                    6у+18у-5у=83-15+3+24

8а=24                                                 19у=95

а=24:8                                                у=95:19

а=3                                                     у=5

2012-04-08T07:44:07+04:00

2а+4-10=18-6а    2а+6а=18+6   8а=24    а=3

проверка   2(3+2)-10=6(3-а)       0=0    ответ а=3

 

 

6у-3+18у-24=83+5у-15    6у+18у-5у=83-15+3+24   19у=95  у=5

проверка 3(10-1)+6(15-4)=83+5(5-3)   27 +66=83+10    93=93

ответ у=5